Kandungan Alginat Sargassum polycystum pada Metode Budidaya dan Umur Tanam berbeda - Dwi Sunu Widyartini; A. Ilalqisny Insan; Sulistyani Sulistyani (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Sargassum polycystum is one of seaweed what be able to produce alginate. Cultivation development intensively use common cultivation methods and planting age of growth season properly which can be able to produce good growth and highest alginate. This study is used an experimental method. The basic design used for the content of alginate S. polycystum use completely randomized design (CRD) with Split Plot Design which repeated 3 times. The main plot of this study is a method of cultivation are included by floatting method and bottom method and Subplot is age after planting are consist of 7, 14, 21 and 28 days. The cultivation result of S. polycystum by bottom method with 28 days, showed the highest growth rate about 17.38 g.day-1, while the lowest growth were founded on bottom method on age 7 days about 3.42 g.day-1. The Results of analysis of variance showed that the interaction of cultivation method and planting age have significant effect on the subtances of alginate from S. polycystum. The highest alginate are produced by bottom method of planting age on 28 days about 58.33%. The Lowest alginate are produced by floating and bottom methods of planting age on 7 days about 11.67%. Quality of alginate farmed bottom methods of color is more yellowish than the cultivation of the floating method.